Environmental preservation in D. Zawawi Imron’s poetry: critical discourse analysis through Madurese sufi perspectives - Izzah, Ismatul; Darni; Mintowati; Yuwana, Setya; Ahmadi, Anas (Penerbit Universiti Kebangsaan Malaysia, 2025)
This study specifically aims to examine the ecocritical values of green environmental preservation in the poems of D. Zawawi Imron through the theoretical framework of Critical Discourse Analysis (CDA). The research data are obtained through an analysis of selected D. Zawawi Imron's poems, including "Gray Musings," "Learning from Fish," and "Land." The findings reveal that D. Zawawi Imron’s poetry mirrors an ecological awareness interwoven with local wisdom, specifically in accentuating religious and cultural values of the Madurese community. At the textual level, the use of metaphors such as "mute," "eternal," "sin," and "blood" in "Gray Musings" first expresses criticisms against environmental destruction and loss of ecological balance. Second, in “Learning from fish,” D. Zawawi Imron’s work conveys a Sufi perspective that views nature as humanity’s spiritual counterpart and fellow creations of God, thereby emphasising the centrality of a harmonious relationship among all beings. Third, “Land” functions as a symbolic medium of resistance against the ideologies of capitalism and anthropocentrism that exploit nature. This study demonstrates the notion that literary works, particularly poetry, play a strategic role in the exaltation of ecological campaigns and ethical reflections in modern societies. Moral and spiritual consciousness, therefore, permeates these poems, seemingly restoring the stabilisation of human-environment relationships.